Can Job Search Assistance Improve the Labour Market Integration for Refugees? Evidence from a Field Experiment - Michele Battisti; Yvonne Giesing; Nadzeya Laurentsyeva (Center for Economic Studies and ifo Institute (CESifo), 2018)
We conducted a field experiment to evaluate the impact of job-search assistance on the employment of recently arrived refugees in Germany. The treatment group received job-matching support: an NGO identified suitable vacancies and sent the refugees' CVs to employers. Results of follow-up phone surveys show a positive and significant treatment effect of 13 percentage points on employment after twelve months. These effects are concentrated among low-educated refugees and those facing uncertainty about their residence status. These individuals might not search effectively, lack access to alternative support programmes, and may be disregarded by employers due to perceived higher hiring costs.
Keywords: E24; F22; J61; J68; 330; refugees; labour market integration; job search assistance; field experiment